Alpha radioisotopes of plutonium in coastal ecosystems of the Black Sea. - Tereshchenko, N N (PANGAEA, 2009)
A study of redistribution of alpha-radioactive isotopes of plutonium, 239,240Pu and 238Pu in coastal ecosystems off the northern Black Sea coast for quantitative characterization of modern radioecological situation in these waters with respect to plutonium was the aim of this work.
(Table 1) Concentration of plutonium isoptopes in dry matter of bottom sediments from the Kerch Straight area in December 2007
Keywords: Alpha spectrometry; Archive of Ocean Data; ARCOD; DEPTH, sediment/rock; Grab; GRAB; Kerch Straight; NNT-2007/12-1; NNT-2007/12-2; NNT-2007/12-3; NNT-2007/12-4; NNT-2007/12-5; NNT-2007/12-6; Plutonium 238; Plutonium 238+239+240; Plutonium 239+240